Cryoenzymology of the hammerhead ribozyme. - Feig, A L (1998)
The technique of cryoenzymology has been applied to the hammerhead ribozyme in an attempt to uncover a structural rearrangement step prior to cleavage. Several cryosolvents were tested and 40% (v/v) methanol in water was found to perturb the system only minimally. This solvent allowed the measurement of ribozyme activity between 30 and -33 degrees C. Eyring plots are linear down to -27 degrees C, but a drastic reduction in activity occurs below this temperature. However, even at extremely low temperatures, the rate is still quite pH dependent, suggesting that the chemical step rather than a structural rearrangement is still rate-limiting. The nonlinearity of the Eyring plot may be the result of a transition to a cold-denatured state or a glassed state.